In-situ X-ray μLaue diffraction study of copper through-silicon vias. (January 2016) - Sanchez, Dario Ferreira; Reboh, Shay; Weleguela, Monica Larissa Djomeni; Micha, Jean-Sébastien; Robach, Odile; Mourier, Thierry; Gergaud, Patrice; Bleuet, Pierre
Abstract: In this work, we developed an original in-situ strain investigation of a Cu through silicon vias (TSVs) sample using X-ray μLaue diffraction mapping. We perform an in-situ investigation of a Cu TSV sample. Three different stages were analysed: (i) at room temperature, (ii) during an annealing at 400 °C and, (iii) at room temperature again after the annealing. In combination with analytical and Finite Element Method analysis, the Cu extrusion and grain growth are identified and quantified, and, their effects on the measured Si strain fields are discussed. Highlights: In-situ strain investigation of a Cu through silicon vias sample using X-ray µLaue diffraction mapping Analysis (i) at room temperature, (ii) during an annealing at 400°C and, (iii) at room temperature again after the annealing Original optimized setup configuration and sample preparation with plasma Focused Ion Beam Analytical and Finite Elements Method approaches combined; the Cu extrusion and grain growth are identified and quantified